Parallel Computing: From Multicores and GPU's to Petascale - Chapman, Barbara (IOS Press, 2013)
Parallel computing technologies have brought dramatic changes to mainstream computing; the majority of today’s PC's, laptops and even notebooks incorporate multiprocessor chips with up to four processors. Standard components are increasingly combined with GPU's (Graphics Processing Unit), originally designed for high-speed graphics processing, and FPGA's (Free Programmable Gate Array) to build parallel computers with a wide spectrum of high-speed processing functions. The scale of this powerful hardware is limited only by factors such as energy consumption and thermal control. However, in addition to hardware factors, the practical use of petascale and exascale machines is often hampered by the difficulty of developing software which will run effectively and efficiently on such architecture. This book includes selected and refereed papers, presented at the 2009 international Parallel Computing conference (ParCo2009), which set out to address these problems. It provides a snapshot of the state-of-the-art of parallel computing technologies in hardware, application and software development. Areas covered include: numerical algorithms, grid and cloud computing, programming – including GPU and cell programming. The book also includes papers presented at the six mini-symposia held at the conference.